2013
DOI: 10.1089/ars.2013.5307
|View full text |Cite
|
Sign up to set email alerts
|

Is Myeloperoxidase a Key Component in the ROS-Induced Vascular Damage Related to Nephropathy in Type 2 Diabetes?

Abstract: It is still unclear whether microvascular complications of type 2 diabetes correlate with leukocyte-endothelium interactions and/or myeloperoxidase (MPO) levels. In the present study, we found that serum levels of glucose, the rate of ROS and MPO concentration were higher in type 2 diabetic patients. Patients with nephropathy (39.6%) presented higher MPO levels that correlate positively with the albumin/creatinine ratio (r = 0.59, p < 0.05). In addition, nephropatic patients showed increased leukocyte-endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 9 publications
5
38
0
Order By: Relevance
“…Oxidative stress has been related to the pathophysiology of a wide variety of diseases (275,276), including cardiometabolic diseases (hypertension, stroke, diabetes, metabolic syndrome), neurodegenerative disorders (Alzheimer's disease [AD], PD, and others), Duchenne muscular dystrophy, chronic obstructive pulmonary disease (COPD), and cancer.…”
Section: Non-targeted Antioxidant Treatmentsmentioning
confidence: 99%
“…Oxidative stress has been related to the pathophysiology of a wide variety of diseases (275,276), including cardiometabolic diseases (hypertension, stroke, diabetes, metabolic syndrome), neurodegenerative disorders (Alzheimer's disease [AD], PD, and others), Duchenne muscular dystrophy, chronic obstructive pulmonary disease (COPD), and cancer.…”
Section: Non-targeted Antioxidant Treatmentsmentioning
confidence: 99%
“…The parallel plate flow chamber in-vitro model has been described in detail elsewhere [26,27]. A Luminex 200 flow analyzer system was used to evaluate ICAM-1, VCAM-1, E-selectin, IL-6 and TNF-alpha in serum from PCOS subjects (Millipore, Austin, TX, USA).…”
Section: Adhesion Assay Levels Of Cytokines and Adhesion Molecules mentioning
confidence: 99%
“…miR-31 also seems to be associated with inflammation and increased interaction between leukocytes and endothelial cells, both common pathological features of diabetic vascular complications [6,30]. Further research is needed to reveal the specific role of this miRNA in the context of T2D in general and specifically in DN, and to confirm its potential as a biological marker of DN.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, leukocytes migrate to the vascular walls in inflammatory situations, a multistep process regulated by cytokines released by leukocytes and adhesion molecules in endothelial cells [27]. We have previously demonstrated that the different steps involved in leukocyte recruitment -namely leukocyte rolling and adhesion -are enhanced in T2D patients and even more pronounced in patients with DN [6]. In the present study, we confirm these observations and also demonstrate a positive correlation between miR-31 and PMN rolling velocity as Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry well as a negative correlation between miR-31 and PMN adhesion, suggesting that the regulation of leukocyte-endothelial cell interactions is associated with the regulation of this miRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation